Evaluation of electrocardiographic parameters in amputee football players - Kurtoğlu, Ahmet; Kurtoğlu, Ertuğrul; Akgümüş, Alkame; Çar, Bekir; Eken, Özgür; Sârbu, Ioan; Ciongradi, Carmen Iulia; Alexe, Dan Iulian; Candussi, Iuliana Laura (Frontiers in Psychology, 2023)
The present study aimed to compare electrocardiographic (ECG) parameters of amputee football players (AF) with football players without disability (FP) and sedentary individuals without disability (SI). A total of 32 participants (AF=9, FP=11, SI=12) were included in the study. ECG parameters including P-wave amplitude, P-wave duration, PR interval, QRS duration, RR interval, QT interval, corrected-QT interval (QTc), ST segment duration, Tp-e duration, Tp-e/QT and Tp-e/QTc ratios were assessed in all the study participants by using a 12-lead ECG device. OneWay Anova Test was used for statistical analysis. Of all ECG parameters, P-wave amplitude and QTc were significantly higher in the AF group in comparision to FP and SI groups. QRS duration was found to be lower in the AF group when compared to FP and SI groups. Myocardial repolarization parameters including Tp-e duration, Tp-e/QT and Tp-e/QTc ratios were similar between groups, as were other parameters such as P-wave duration, PR interval, RR interval, QRS duration and QT interval. It was found that some ECG parameters of amputee football players differ from those with non-disabled players and non-disabled sedentary individuals. These different parameters were within normal limits.